2020
DOI: 10.3390/agronomy10030390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity Stress on Phenylpropanoid Genes Expression and Related Gene Expression in Wheat Sprout

Abstract: The effect of salinity (NaCl treatment) on the nutritive value of wheat sprouts was investigated by analyzing the expression of phenylpropanoid biosynthetic pathway genes and the levels of phenylpropanoid compounds. Treatment with various concentrations of NaCl (50, 100, and 200 mM) resulted in increased epicatechin levels but decreased accumulation of catechin hydrate, benzoic acid, and quercetin compounds in the sprouts compared with the control (0 mM). The trans-cinnamic acid, 4-hydroxybenzoic acid, ferulic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Several studies that focused on flavan-3-ols levels under drought stress reported reduced levels of flavan-3-ols in juvenal plants [ 110 , 111 ]; while in more mature plants, flavanol levels increased under drought stress [ 112 , 113 ]. Similarly, salt stress increased epicatechin levels, but decreased accumulation of catechin hydrate and quercetin compounds in wheat sprouts compared to the control [ 114 ]. This might be an indication of the crucial role of 4′, 5′-dihydroxy positions in flavonoid structures when dealing with salt stress.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Several studies that focused on flavan-3-ols levels under drought stress reported reduced levels of flavan-3-ols in juvenal plants [ 110 , 111 ]; while in more mature plants, flavanol levels increased under drought stress [ 112 , 113 ]. Similarly, salt stress increased epicatechin levels, but decreased accumulation of catechin hydrate and quercetin compounds in wheat sprouts compared to the control [ 114 ]. This might be an indication of the crucial role of 4′, 5′-dihydroxy positions in flavonoid structures when dealing with salt stress.…”
Section: Flavonoidsmentioning
confidence: 99%
“…We observed that with increases in the concentration of NaCl, all growth parameters steadily decreased. Several previous studies have shown a significant reduction due to salinity in the growth of different plant species, including Fagopyrum tataricum, 10 Triticum aestivum, 31 Sesamum indicum, 32 Carthamus tinctorius, 7 Vigna radiata, 33 Cassia angustifolia, 34 pakchoi, 35 and Pisum sativum. 36 In C. tinctorius, the total flavonoid content was gradually increased by increasing the salinity concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Cuong et al 31 asserted that NaCl, especially at concentrations of 50, 100, and 200 mM, enhanced the levels of epicatechin, but reduced the levels of catechin, benzoic acid, and quercetin in tartary buckwheat sprouts when compared with the control treatment without NaCl. The findings of this study coincide with those of Kim et al 10 and Cuong et al, 31 as we found that treatment with up to 200 mM NaCl enhanced the levels of accumulation of the following phenolic compounds: 4-hydroxybenzoic acid, catechin, ferulic acid, and benzoic acid, but decreased the amounts of caffeic acid, chlorogenic acid, and pcoumaric acid. Kim et al 10 reported a significant increase in the growth of tartary buckwheat sprouts after application of 0.1-1.0 mM betaine, which is supported by our current findings, whereas the addition of different concentrations of betaine, especially at 0.5 mM, enhanced the growth of sprouts of safflower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations